Alangan Mangyans’ Household Coping Strategy During Food Shortage in Occidental Mindoro, Philippines - Declaro-Ruedas, Mary Yole Apple (Journal of Agricultural Studies, 2022)
The study was conducted to determine the household coping strategy employed by the Alangan Mangyans during food shortage in Sablayan & Sta Cruz, Occidental Mindoro, Philippines. The study employed a descriptive design. The research instrument used were the Radimer/Cornell Hunger and Food Insecurity Instrument and Coping Strategy Index (CSI). The Alangans are middle-aged with an average age of 41 years old. They have medium average household sizes of five persons per household, had only reached lower secondary education. They experienced “food insecure without hunger,” which resulted to employing dietary change. The Alangan Mangyan households are considered poor due to low agricultural production and lack of diversified sources of income which resulted in the adequate food supply in the household. The low agricultural production is the “highly serious problem” related to food security because of this, they change their diet relying on less preferred plant food sources and cheaper instant foods readily available in the community.